Geochemical insight into differences in the physical structures and dynamics of two adjacent maar lakes at Mt. Vulture volcano (southern Italy). (6th May 2013) - Caracausi, A.; Nicolosi, M.; Nuccio, P. M.; Favara, R.; Paternoster, M.; Rosciglione, A.
Abstract: [1] We report on the first geochemical investigation of the Monticchio maar lakes (Mt. Vulture volcano, southern Italy) covering an annual cycle that aimed at understanding the characteristic features of the physical structures and dynamics of the two lakes. We provide the first detailed description of the lakes based on high‐resolution conductivity‐temperature‐depth (CTD) profiles, chemical and isotopic (H and O) compositions of the water, and the amounts of dissolved gases (e.g., He, Ar, CH4, and CO2 ). The combined data set reveals that the two lakes, which are separated by less than 200 m, exhibit different dynamics: one is a meromictic lake, where the waters are rich in biogenic and mantle‐derived gases, while the other is a monomictic lake, which exhibits complete turnover of the water in winter and the release of dissolved gases. Our data strongly suggest that the differences in the dynamics of the two lakes are due to different density profiles affected by dissolved solutes, mainly Fe, which is strongly enriched in the deep water of the meromictic lake. A conceptual model of water balance was constructed based on the correlation between the chemical composition of the water and the hydrogen isotopic signature. Gas‐rich groundwaters that feed both of the lakes and evaporation processes subsequently modify the water chemistry of the lakes. Our data highlight that no further potential hazardous accumulation of lethal gases is expected at the Monticchio lakes. Nevertheless, geochemical monitoring is needed to prevent the possibility of vigorous gas releases that have previously occurred in historical time. Key Points: Geochemstry of different dynamics of two adjacent maar lakes A new conceptual model of water balance was constructed The dynamics of the lakes are due to different amounts of solutes in the water